2022
DOI: 10.1038/s41598-022-18426-y
|View full text |Cite
|
Sign up to set email alerts
|

Current trends and outcomes of non-elective neurosurgical care in Central Europe during the second year of the COVID-19 pandemic

Abstract: Reflecting the first wave COVID-19 pandemic in Central Europe (i.e. March 16th–April 15th, 2020) the neurosurgical community witnessed a general diminution in the incidence of emergency neurosurgical cases, which was impelled by a reduced number of traumatic brain injuries (TBI), spine conditions, and chronic subdural hematomas (CSDH). This appeared to be associated with restrictions imposed on mobility within countries but also to possible delayed patient introduction and interdisciplinary medical counseling.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…After removing duplicates, 935 articles were left; their titles and abstracts were screened, and 78 relevant articles were identified for full-text review. Overall, this study collated data and information from 49 articles, [ 11 , 12 , 17 , [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] , [47] , [48] , [49] , [50] , [51] , [52] , [53] , [54] , [55] , [56] , [57] , [58] , [59] , [60] , [61] , [62] , [63] , [64] , [65] ] with 25 of them included in the quantitative synthesis ( Figure 1 ). Twenty-two of these articles were retrospective in nature, two had data collected both retrospectively and prospectively, one was both a retrospective cohort study and a survey.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…After removing duplicates, 935 articles were left; their titles and abstracts were screened, and 78 relevant articles were identified for full-text review. Overall, this study collated data and information from 49 articles, [ 11 , 12 , 17 , [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] , [47] , [48] , [49] , [50] , [51] , [52] , [53] , [54] , [55] , [56] , [57] , [58] , [59] , [60] , [61] , [62] , [63] , [64] , [65] ] with 25 of them included in the quantitative synthesis ( Figure 1 ). Twenty-two of these articles were retrospective in nature, two had data collected both retrospectively and prospectively, one was both a retrospective cohort study and a survey.…”
Section: Resultsmentioning
confidence: 99%
“…Majority of the included studies observed a significant decrease in overall caseloads, both surgical and non-surgical, resulting in diminished clinical exposure for residents. [ 12 , [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [30] , [31] , [32] , [33] , 35 , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] , [47] , [48] , [49] , [50] , [51] , [52] , [53] , [54] , [56] , [57] , [58] , [59] , [60] , [61] , [62] , [63] , [64] , [65] ] Ashry et al found that 56% of the residents had a reduction in their actual role in the surgical steps and the number of residents scrubbing in the same procedure had been decreased to the minimum for preservation of personal protective equipment (PPE). [21] A survey completed by El-Ghandour and colleagues revealed that elective surgery/clinic cancellation occurred more frequently in African countries and that theyr were utilizing PPE significantly less commonly in LMICs (OR=0.441, 95% CI 0.216-0.900, p <0.05).…”
Section: Resultsmentioning
confidence: 99%
“…[ 4 ] With regard to the reductions seen in the “ Neuro-Oncology ” and “ Functional ” subspecialties, we suggest that this may be due to a decline in the number of craniotomies, occipital nerve, deep brain, and spinal cord stimulation. A reduced incidence of more chronic conditions, including spine conditions, hydrocephalus, and chronic subdural hematomas,[ 18 ] perhaps as a result of patient reluctance to present clinically, may have also contributed to our trends. However, uncertainty remains as we are unable to elicit whether the reductions seen across these three subspecialties are merely attributed to outliers seen between 2019 and 2020 and unrelated to the pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…A similar finding was reported by Lara-Reyna [ 33 ]. On the contrary, a study from the Czech Republic and Austria showed no difference in all subgroups of patients treated for TBIs [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Official recommendations were [ 35 ] established [ 8 ] to maintain the emergency care system. The authors of two studies [ 23 , 34 ] concerned with the non-elective neurosurgical procedures in central and eastern Europe have shown no difference in volume during the pandemic.…”
Section: Discussionmentioning
confidence: 99%